Effect of Stabilized Products of Sorghum Enriched with Lactobacilli (SPSL) on Growth Performance, Haematological Parameters and Ileal Microflora of Guinea Fowl Broilers (Numida meleagris) - Libanio, D.; Bouassi, T.; Kouame, E.Y.A.; Oke, O.E.; Houndonougbo, F.M.; Chrysostome, A.A.M.C.; Tona, K. (International Journal of Poultry Science, 2020)
Objective: This experiment was conducted to investigate the effects of Stabilized products of sorghum enriched with lactobacilli (SPSL) on growth performance, haematological parameters and ileal microflora of Guinea fowl. Materials and Methods: A total of 520 one day old guinea fowls with average body weight of 33.02g were assigned to 4 treatments with 5 replicates (26 birds/replicate). The 4 treatments were: (1) Only basal diet (T–), (2) Basal diet supplemented with antibiotics in water (T+), (3) Basal diet supplemented with the SPSL at the dose of 1.5% (T1.5), (4) Basal diet supplemented with SPSL at the dose of 3% (T3). At 12 week of age, blood samples were collected from 40 birds per treatment for haematological analysis. The birds were also slaughtered and ileal contents were harvested for microbiological analysis. Results: The results showed that there were no significant differences in the feed intake, feed conversion ratio and body weights of the birds across the treatments. Weight and length of intestine, caeca length and abdominal fat of the birds in T3 were higher (p<0.05) than those of the other treatment groups. The lymphocyte in T1.5 group was higher than those of T– group (p <0.05). Total coliforms bacteria was higher in the birds of T+ and T– treatment groups than those of T1.5 and T3. The level of Escherichia coli was lower (p<0.05) in the birds of T3 group compared to other treatment groups. Total coliforms in T1.5 and T3 birds were lower than those of T– and T+. Conclusion: It was concluded that the SPSL significantly improved the intestinal parameters and reduced the potential pathogen bacteria.